Quantifying morphological features of actin cytoskeletal filaments in plant cells based on mathematical morphology. (21st January 2016) - Kimori, Yoshitaka; Hikino, Kazumi; Nishimura, Mikio; Mano, Shoji
Abstract: By quantifying the morphological properties of biological structures, we can better evaluate complex shapes and detect subtle morphological changes in organisms. In this paper, we propose a shape analysis method based on morphological image processing, and apply it to image analysis of actin cytoskeletal filaments in root hair cells of Arabidopsis thaliana . In plant cells, the actin cytoskeletal filaments have critical roles in various cellular processes such as vesicle trafficking and organelle motility. The dynamics of vesicles and organelles in plant cells depend on actin cytoskeletal filaments, regulating cell division and cell enlargement. To better understand the actin-dependent organelle motility, we attempted to quantify the organization of actin filaments in the root hair cells of the root hair defective 3 ( rhd3 ) mutant. RHD3 is involved in actin organization, and its defect has been reported to affect the dynamics of various vesicles and organelles. We measured three shape features of the actin filaments in wild-type and mutant plants. One feature (thickness) was depicted on a grayscale; the others (describing the complexity of the filament network patterns in two-dimensional space) were depicted as binary features. The morphological phenotypes of the cytoskeletal filaments clearly differed between wild-type and mutant. Subtle variations of filament morphology among the mutants were detected and statistically quantified. Highlights: We proposed a shape analysis method based on mathematical morphology for structural characterization of biological entities. The approach was applied to morphological analysis of actin cytoskeletal organization in the root hairs of Arabidopsis thaliana . We quantified thickness distribution, orientation distribution and complexity of actin filaments in the wild-type and mutant cells. We identified clear differences of the morphological phenotypes of the filaments between the wild-type and mutant cells, and found subtle differences among the filaments of mutant cells.